Estudo comparativo entre a coleta seletiva do lixo no município brasileiro de São José dos Campos – SP e do bairro Southwark, em Londres - Paquet, Luciana Leite (2012)
This paper aims at studying the recyclable collection of the solid waste in São José dos Campos – São Paulo, Brazil, which was one of the pacesetters in the recyclable waste and is now one of the benchmarks in the country. In addition to presenting the history and the process of recycling collection in such municipality, this paper also showed the history and the process of recycling collection in the London Borough of Southwark, England. Comparing both processes led to a better understanding of how ahead recyclable collection of the solid waste is in São José dos Campos. The comparison also highlighted the cultural and strategic differences between both processes and enabled the visualization of new opportunities of improvement for the treatment of recyclable waste in São José dos Campos.The final part of this paper brings suggestions that could be applied to improve the treatment of recyclable waste in the municipality studied.